The Relationship Between BOD Ethical Commitment and Risk Management and Internal Control System with the Performance of Shariah-Compliant Companies - Nurul ‘Athirah Rosli; Hasnah Haron; Muhammad Shabir Shaharudin (Penerbit UMP, 2024)
Volume: 5 No : 3 (page: 393–407)